The resolution function and effective response of piezoelectric thin films in Piezoresponse Force Microscopy - Morozovska, A.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
The elastic Green function and resolution function in Piezoresponse Force Microscopy (PFM) of thin piezoelectric film capped on the rigid substrate are derived. The extrinsic size effect on the resolution function is demonstrated.